Estágio supervisionado obrigatório relato de caso: artrodese pancarpal minimamente invasiva em cão - Borges, Ryshely Sonaly de Moura (Universidade Federal Rural do Semi-Árido, 2021)
Mandatory supervised internship is essential during graduation in veterinary medicine; being the opportunity for students in training to know their area of expertise, expand their skills and join theory to practice, which is an essential educational and professionalizing link. In this context, this work aims to describe the activities performed in the internship and especially to report a surgical case that occurred in this period, of an adult, mixed breed, male, 21.6 kg dog with a history of having suffered a gunshot wound in the left thoracic limb about 5 days ago, with functional impotence and instability of the wrist joint since then. After physical, orthopedic and radiographic evaluations, the presence of several fractures in carpal and metacarpal bones was verified. The patient underwent pancarpal arthrodesis as treatment, followed by transsurgical radiography. After 15 days, he returned to the clinic for stitch removal, supporting the limb, with normal gait, with no apparent discomfort. Thus, it can be concluded that the supervised internship is important in acquiring knowledge and improving the practice, providing daily contact with cases with different etiologies and treatments; and that pancarpal arthrodesis is an effective therapeutic method, with good results in terms of pain resolution, limb function and maintenance, considering that this surgical technique avoids amputation; being beneficial to the patient and the tutor.
Keywords: Ferimentos balísticos; Fusão articular; Ortopedia veterinária; CIENCIAS AGRARIAS::MEDICINA VETERINARIA